2008
DOI: 10.1074/mcp.m700543-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Interaction Chromatography Reduces the Complexity of the Phosphoproteome and Improves Global Phosphopeptide Isolation and Detection

Abstract: The diversity and complexity of proteins and peptides in biological systems requires powerful liquid chromatography-based separations to optimize resolution and detection of components. Proteomics strategies often combine two orthogonal separation modes to meet this challenge. In nearly all cases, the second dimension is a reverse phase separation interfaced directly to a mass spectrometer. Here we report on the use of hydrophilic interaction chromatography (HILIC) as part of a multidimensional chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
304
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(315 citation statements)
references
References 33 publications
7
304
2
2
Order By: Relevance
“…Kokubu and co-workers showed that 0.1% TFA, 50% ACN as IMAC loading buffer reduced the level of nonspecific binding and improved the specificity of the method toward phosphopeptides [56]. Yet another approach to improve the performance of IMAC is to reduce the complexity of the peptide samples by prefractionation using methods such as IEF [57][58][59][60], Ion Exchange Chromatography [41,43,46,61] or hydrophilic interaction chromatography (HILIC) [62] prior to IMAC purification.…”
Section: Immobilized Metal Ion Affinity Chromatographymentioning
confidence: 99%
See 3 more Smart Citations
“…Kokubu and co-workers showed that 0.1% TFA, 50% ACN as IMAC loading buffer reduced the level of nonspecific binding and improved the specificity of the method toward phosphopeptides [56]. Yet another approach to improve the performance of IMAC is to reduce the complexity of the peptide samples by prefractionation using methods such as IEF [57][58][59][60], Ion Exchange Chromatography [41,43,46,61] or hydrophilic interaction chromatography (HILIC) [62] prior to IMAC purification.…”
Section: Immobilized Metal Ion Affinity Chromatographymentioning
confidence: 99%
“…These hydrogen bonds can subsequently be disrupted by decreasing the organic environment in the mobile phase and peptides will elute according to their polarities (hydrophilicities). McNulty and Annan introduced HILIC as a peptide prefractionation technique prior to phosphopeptide enrichment by IMAC [62]. Using a TSKgel Amide-80 HILIC column and a shallow inverse organic gradient of ACN, water and TFA, they fractionated 1 mg of tryptic peptides from HeLa cells, which had been starved and treated with the phosphatase inhibitor, calyculin A.…”
Section: Hydrophilic Interaction Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…An incredible number of HILIC stationary phases have been reported for diverse selective and specialized applications to a range of analytes. Accordingly, in recent years, HILIC has experienced a dramatic growth for proteomic applications, ranging from the separation of complex peptide mixtures [28,29], to the enrichment of subproteomes, such as phosphorylated [30] or glycosylated peptides [31], or N-terminally acetylated peptides [29], usually before Bottom Up mass spectrometry is applied.…”
Section: Up Front Intact Protein Separationmentioning
confidence: 99%